A inclusão escolar de alunos com deficiências: análise do conceito - Moreno, Soraya Ramirez (2009)
The present study had the purposed of analyzing the concept of school inclusion - having students with deficiencies as primary focus - as expressed in educational and psychological literature. The search for publications was done at PEPSIC and SCIELO inside CAPES website, educational online bases and manual search in books and papers published from 1994 to 2008. Four elements were analyzed linked to the concept of school inclusion: the target population, the principles that underlay school inclusion, the school inclusion objectives and school inclusion policies. As a result, it was verified that school inclusion is a wide-ranging concept, inserted in a wide social inclusion concept; the basic principles behind it were already built-in in the first education initiatives to the people with deficiencies. The origins of problematic aspects of school inclusion have been identified and discussed. It was concluded that, being a complex matter, there is not a single concept of school inclusion of students with deficiencies. Such a diversity of conceptions may be due to the fact that the population that seeks/has to be included has grown and collisions appeared between the regular school and the special school as holders of the education of students with deficiencies